Prelemniscal Radiations Neuromodulation in Parkinson Disease´s Treatment - Carrillo-Ruiz, José D.; Velasco, Francisco; Jiménez, Fiacro; Velasco, Ana Luisa; Castro, Guillermo; Soto, Julián; Salcido, Victor (IntechOpen, 2012)
None